The Effect of SiJaring LMS-Based Learning Model in Fostering Self-Regulated Learning among Islamic Education Students in Indonesia - Sugiyono, Sugiyono; Nasir, Muhammad; Tahir, M. (Dinamika Ilmu, 2023)
This research aimed to investigate the effectiveness of the SiJaring Learning Management System (LMS)-based learning model in the Islamic Civilization History course at Islamic Religious Higher Education institutions in East Kalimantan, Indonesia. The study employed a quantitative research approach with a quasi-experimental design. A total of 320 respondents were selected as research participants from a population of 1,890. Data was collected through questionnaires administered to two groups, namely the experimental group and the control group. Each respondent underwent pretest and posttest sessions. Statistical analysis using SPSS revealed a significant difference in mean scores between the pretest and posttest results of the experimental group, with a mean difference of 45.61. Furthermore, the independent t-test demonstrated a significant difference in mean scores between the experimental and control groups' post-test results, with a mean difference of 45.1234. These findings indicate that the implementation of the SiJaring LMS-based learning model effectively promotes self-regulated learning among students in the Islamic Civilization History course at Islamic Religious Higher Education institutions in East Kalimantan, Indonesia.